- #1

jupiter_8917

- 5

- 0

Solve the equation

log (little 3) X + log (little6) X = 2

the answer is 3.9

Here is what I try

log (little 6)x = log (little 3)x/log (little 3)6 = log (little 3) (x-6)log (little 3)x + log (little 3) (x-6) = 2

log (little3) (x(x-6)) =2

log (little3) (x^2-6x)=3^2

x^2 -6x =9

x^2-6x-9=0

x= 7.2 and -1.2 and of course it is not the right answer

can anyone please explain how do you get 3.9? Thank you

log (little 3) X + log (little6) X = 2

the answer is 3.9

Here is what I try

log (little 6)x = log (little 3)x/log (little 3)6 = log (little 3) (x-6)log (little 3)x + log (little 3) (x-6) = 2

log (little3) (x(x-6)) =2

log (little3) (x^2-6x)=3^2

x^2 -6x =9

x^2-6x-9=0

x= 7.2 and -1.2 and of course it is not the right answer

can anyone please explain how do you get 3.9? Thank you

Last edited: